Effect of portal hypertension in the small bowel: an endoscopic approach - Figueiredo, P (2008)
BACKGROUND AND AIM: The effects of portal hypertension in the small bowel are largely unknown. The aim of the study was to prospectively assess portal hypertension manifestations in the small bowel. METHODS: We compared, by performing enteroscopy with capsule endoscopy, the endoscopic findings of 36 patients with portal hypertension, 25 cirrhotic and 11 non-cirrhotic, with 30 controls. RESULTS: Varices, defined as distended, tortuous, or saccular veins, and areas of mucosa with a reticulate pattern were significantly more frequent in patients with PTH. These two findings were detected in 26 of the 66 patients (39%), 25 from the group with PTH (69%) and one from the control group (3%) (P < 0.0001). Among the 25 patients with PTH exhibiting these patterns, 17 were cirrhotic and 8 were non-cirrhotic (P = 0.551). The presence of these endoscopic changes was not related to age, gender, presence of cirrhosis, esophageal or gastric varices, portal hypertensive gastropathy, portal hypertensive colopathy, prior esophageal endoscopic treatment, current administration of beta-blockers, or Child-Pugh Class C. More patients with these endoscopic patterns had a previous history of acute digestive bleeding (72% vs. 36%) (P = 0.05). Active bleeding was found in two patients (5.5%). CONCLUSIONS: The presence of varices or areas of mucosa with a reticulate pattern are manifestations of portal hypertension in the small bowel, found in both cirrhotic and non-cirrhotic patients. The clinical implications of these findings, as regards digestive bleeding, are uncertain, although we documented acute bleeding from the small bowel in two patients (5.5%).